Extra-Chromosomal DNA Sequencing Reveals Episomal Prophages Capable of Impacting Virulence Factor Expression in Staphylococcus aureus - Deutsch, Douglas R.; Utter, Bryan; Verratti, Kathleen J.; Sichtig, Heike; Tallon, Luke J.; Fischetti, Vincent A. (Frontiers in Microbiology, 2018)
Staphylococcus aureus is a major human pathogen with well-characterized bacteriophage contributions to its virulence potential. Recently, we identified plasmidial and episomal prophages in S. aureus strains using an extra-chromosomal DNA isolation and sequencing approach, uncovering the plasmidial phage phiBU01, which was found to encode important virulence determinants. Here, we expanded our extra-chromosomal sequencing of S. aureus, selecting 15 diverse clinical isolates with known chromosomal sequences for extra-chromosomal DNA isolation and next-generation sequencing. We uncovered the presence of additional episomal prophages in 5 of 15 samples, but did not identify any plasmidial prophages. Extra-chromosomal DNA isolation was found to enrich for circular prophage elements, and qPCR characterization of the strains revealed that such prophage enrichment is detectable only in extra-chromosomal DNA samples and would likely be missed in whole-genome DNA preparations (e.g., detection of episomal prophages did not correlate with higher prophage excision rates nor higher excised prophage copy numbers in qPCR experiments using whole-genome DNA). In S. aureus MSSA476, we found that enrichment and excision of the prophage phiSa4ms into the cytoplasm was temporal and that episomal prophage localization did not appear to be a precursor to lytic cycle replication, suggesting Sa4ms excision into the cytoplasm may be part of a novel lysogenic switch. For example, we show that phiSa4ms excision alters the promoter and transcription of htrA2, encoding a stress-response serine protease, and that alternative promotion of htrA2 confers increased heat-stress survival in S. aureus COL. Overall, extra-chromosomal DNA isolation and focused sequencing may offer a more complete genomic picture for bacterial pathogens, offering insights into important chromosomal dynamics likely missed with whole-genome DNA-based approaches.